Exploring board composition and humanistic management in developing countries' State-Owned Enterprises - Zvitambo, Kudakwashe; Magodhini, Prisca; Masinire, Sharon (Goodwood Publishing, 2025)
Purpose: This study examines the impact of board composition on the humanistic management performance of Zimbabwean State-Owned Enterprises (SOEs). This study examines four essential factors of board composition–board diversity, board tenure, board size, and board committees—to determine their influence on governance and performance in SOEs. Methods: A descriptive research design with an interpretative qualitative approach was adopted. Data were collected from Zimbabwe General Auditor Reports (2016-2022) and semi-structured interviews with 20 SOE directors. Thematic analysis was used to identify patterns and develop insights into the relationship between board composition and humanistic management performance. Results: The findings revealed that political interference, inadequate board evaluation, and the appointment of unqualified directors negatively affect board composition, limiting SOEs' ability to achieve humanistic management outcomes. Despite the existence of governance frameworks, these challenges hinder effective decision-making, transparency, and strategic alignment with humanistic management principles. Conclusions: The study concludes that board size does not affect the humanistic management performance of the board. Limitations: The study is limited to Zimbabwean SOEs, which may affect the generalizability of the findings to other developing economies. Additionally, reliance on qualitative methods introduces the possibility of subjective biases despite rigorous thematic analysis. Contribution: This study recommends that Parliament Portfolio Committees strengthen their oversight role in board appointments to enhance governance and performance. It also advocates adopting a Humanistic Governance Framework to improve transparency, accountability, and efficiency while reducing corruption in Zimbabwean SOEs.